(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This study presents the results of a comparative morphological evaluation of the spleen during late postnatal ontogenesis under the influence of chronic nicotine-alcohol intoxication and subsequent therapeutic intervention. Structural alterations in the parenchyma and stroma of the spleen were identified under toxic stress, as well as the efficacy of corrective treatment based on hepatoprotective and antioxidant agents. Histological and morphometric techniques were used to objectively assess the severity of pathological changes and the extent of tissue regeneration.